2007
DOI: 10.1080/08860220701569846
|View full text |Cite
|
Sign up to set email alerts
|

Early Renal Injury Induced by Caffeine Consumption in Obese, Diabetic ZSF1Rats

Abstract: Our previous studies indicate that prolonged caffeine consumption exacerbates renal failure in nephropathy associated with the metabolic syndrome. Reduced activity of the antioxidant defense system and beneficial effects of antioxidant therapy have been reported in diabetic rats and humans. The purpose of this study was to examine the early renal effects of caffeine consumption and the effects of concomitant antioxidant therapy in young obese, diabetic ZSF1 rats. Eleven-week-old male ZSF1 rats were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 49 publications
4
44
0
Order By: Relevance
“…40 The conceptual view of CKD treatment at an early stage can take also advantage of the clinical nutritional information of this study. We envisage that approaches addressed at the change of lifestyle/environmental factors could be favorable for renal artery responsiveness under relatively stressful conditions, for example, in arterial hypertension and in conditions with increased pulse pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 The conceptual view of CKD treatment at an early stage can take also advantage of the clinical nutritional information of this study. We envisage that approaches addressed at the change of lifestyle/environmental factors could be favorable for renal artery responsiveness under relatively stressful conditions, for example, in arterial hypertension and in conditions with increased pulse pressure.…”
Section: Discussionmentioning
confidence: 99%
“…37 Long-term consumption of beverages containing caffeine such as coffee and green tea is associated with a reduced risk of type 2 diabetes mellitus; in healthy subjects daily caffeine intake reduces insulin sensitivity 38 ; the vascular repair mechanism is adequately functional in the early stage of CKD. 39,40 In experimental models, caffeine attenuated the endotoxin-induced release of cytokines and augmented endotoxin-induced increases in plasma catecholamines and PRA: caffeine, most likely through the interaction with adenosine receptors and interference with antiinflammatory and/or glomerular hemodynamic effects of adenosine, augments proteinuria and stimulates some of the key proliferative mechanisms involved in glomerular remodeling and sclerosis. 41 Adenosine is an endogenous nucleoside with potent vasodilatory capacities: its mechanisms of action, however, remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, long-term treatment with caffeine reduced renal function and augmented proteinuria in obese diabetic ZSF1 rats despite improving glucose tolerance. Caffeine-induced renal deterioration was paralleled by enhanced fibrosis, proliferation, and inflammation (Tofovic et al 2002; Tofovic et al 2007). In addition to stimulating the release of renin, the effects of caffeine may be mediated through interference with the direct anti-inflammatory effects of adenosine (Tofovic et al 2007).…”
Section: Disease and Therapeutic Aspectsmentioning
confidence: 99%
“…A previous study has demonstrated that the kidney disease of these rats is mostly independent on hypertension and/or hypertensive nephropathy [45], suggesting the attribution of renal pathophysiology strictly to other components of MetS, such as obesity and/or hyperglycemia. Indeed, many studies in literature use these rats as an appropriate model for the purposes of investigating MetS-related kidney disease or DN [28,46]. Our data show that the daily intake of WGP had no impact on the bodyweight or obesity of these rats (Figure 1).…”
Section: Discussionmentioning
confidence: 59%